A distributed queueing random access protocol for a broadcast channel. - Xu, Wenxin (Computer communication review.)
For decades there has been a search for a multiple access protocol for a broadcast channel that would provide a performance that approached that of the ideal M/D/1 queue. This ideal performance would provide immediate access at light loads and then seamlessly move to a reservation system at high offered loads. DQRAP (distributed queueing random access protocol) provides a performance which approaches this ideal. Furthermore it is accomplished using as few as three control minislots which suggests that, aside from establishing new theoretical bounds, DQRAP will be of great practical value.DQRAP requires that channel time be divided into slots each of which consists of one data slot and m control minislots, and that each station maintain two common distributed queues. One queue is called the data transmission queue, or simply TQ, used to organize the order of data transmission, the other queue is the collision resolution queue, or simply RQ, which is used to resolve the collisions and to prevent collisions by new arrivals. The protocol includes data transmission rules, request transmission rules and queuing discipline rules. Modelling and simulation indicate that DQRAP, using as few as 3 minislots, achieves a performance level which approaches that of a hypothetical perfect scheduling protocol, i.e., the M/D/1 system, with respect to throughput and delay. DQRAP could prove useful in packet radio, satellite, broadband cable, cellular voice, WAN, and passive optical networks.